Sistem Informasi Seleksi Calon Mahasiswa Berbasis Web di Sekolah Tinggi Teknik Musi Palembang - Catur Eri Gunawan; Muhammad Ramadhan; Indrawan Indrawan (JUITA : Jurnal Informatika, 2013)
Sekolah Tinggi Teknik (STT) Musi Palembang is an educational institution. Along with the development of information and communication technology, Sekolah Tinggi Teknik (STT) Musi continually strive to improve the quality of care, such as the ease of dissemination of information and especially new admissions process. Efforts have been made to the campaign to schools both in urban areas as well as through print and electronic media, especially information technology. One of the information technologies that is widely used at present is capable of providing web-based information in the form of text, images, sound, and animation. Currently, Sekolah Tinggi Teknik (STT) Musi not have a software application for admission. The selection system software will be built for the new students by leveraging web -based technologies. In this final project, the authors use a model of Waterfall model and structured paradigm. The programming language used PHP using MySQL database. This software has been tested by using localhost. Result of this research is a web-based information systems student selection.